Green Synthesis of Iron Oxide Nanoparticles and Their Antibacterial Efficacy against Carbapenem-resistant Klebsiella pneumoniae in Bloodstream Infections - Rahul Harikumar Lathakumari; Leela Kakithakara Vajravelu; Jayaprakash Thulukanam; Vishnupriya Panneerselvam; Poornima Baskar Vimala; Dakshina Manoj Nair; Sujith Sri Surya Ravi (Biomedical and Biotechnology Research Journal)
Background: Carbapenem-resistant Klebsiella pneumoniae (CRKP) poses a significant threat to global public health by rendering traditional antibiotic treatments ineffective. The increasing resistance to carbapenems and other critical antibiotics highlights an urgent need for alternative therapeutic strategies. Methods: We analyzed 180 Gram-negative bacilli isolates from blood specimens, of which 30 were identified as CRKP. Antibiotic susceptibility testing was conducted to determine resistance patterns, while genotypic analysis was performed to detect carbapenemase genes, including blaOXA-48, blaVIM, and blaNDM. In addition, we investigated the antibacterial potential of iron oxide nanoparticles (IONPs) synthesized through green methods using Chaetomorpha antennina (C. antennina). The minimum inhibitory concentration (MIC) for both bare and capped nanoparticles was determined to assess their effectiveness against CRKP. Results: The CRKP isolates exhibited total resistance to carbapenems, cefepime, ceftazidime, and piperacillin/tazobactam. Genotypic analysis revealed the presence of blaOXA-48 in 100% of isolates, blaVIM in 93%, and blaNDM in 70%, indicating a diverse array of carbapenemase genes. The green-synthesized IONPs demonstrated potent antibacterial activity against CRKP, with a MIC of 0.15 mg/mL, effectively reducing genomic resistance in the tested isolates. Conclusion: This study underscores the alarming prevalence of antibiotic resistance in CRKP and highlights the need for alternative therapeutic approaches. The promising results from the use of IONPs synthesized from C. antennina suggest that sustainable nanotechnology could be a viable intervention to combat carbapenem resistance in Klebsiella pneumoniae. These findings warrant further investigation into nanoparticle-based therapies for multidrug-resistant organisms.